Analysis of 3800-year-old Yersinia pestis genomes suggests Bronze Age origin for bubonic plague - Maria A. Spyrou (Nature Portfolio, 2018)
Yersinia pestis has caused infections (plague) in humans since the Early Bronze Age (5000 years ago). Here, Spyrou et al. reconstruct Y. pestis genomes from Late Bronze Age individuals, and find genomic evidence compatible with flea-mediated transmission causing bubonic plague.